Issues of consumerism in Bangladesh: present status and challenges - Solaiman, Mohammed; Yasmin, Sanoara; Haque, A. K. M. Ahasanul (IJSRP.ORG, 2012)
Consumerism is the organized movements of conscious consumers against the sellers to protect their rights. Extant consumerism literature mainly focused on developed countries while the conditions of developing countries are largely ignored by the researchers. This paper is an effort to explore the present status, related issues and challenges of consumerism in Bangladesh, i.e. from a developing country perspective. Empirical data, however, evidence that 85 percent of the sample respondents are away from consumerism. The collected data reveals that the areas of consumer deception are adulteration, miss-branding, poor sales service, deception in advertising and poor marketing information system etc. Further, the survey results identified that the factors of consumer deception are - illiteracy, lack of consumer consciousness, absence of consumer legislation, inadequate role of consumer interest groups and indifference of law enforcing agencies, etc. Finally, the paper recommends in support of healthy growth of consumerism global context in general and in Bangladesh in particular.